PROBLEM KEDISIPLINAN MAHASISWA PROGRAM STUDI MANAJEMEN PENDIDIKAN ISLAM DALAM KULIAH DARING MENGHADAPI PANDEMIK CORONA VIRUS DESEASE-2019 DI FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM NEGERI MADURA - Halimatus Sa'adah; Ali Nurhadi (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2020)
Discipline character should be created from all aspects of the activities carried out, including the discipline in following lecture activities carried out online by students of the Islamic Education Management Study Program at IAIN Madura. This research includes a qualitative approach with a descriptive type, the results of the study show that: first, the strategies used to discipline students in online lectures include clarifying pre-course contracts or course objectives, providing subject matter with the discussion method, giving assignments as material to evaluate the material presented and collecting tasks using deadlines. The two supporting factors are so that discipline in online lectures includes communication tools such as cellphones, laptops, and other applications as a medium for conveying information between students and lecturers, and the three inhibiting factors are not facilitated by internet networks and internet quota packages that are owned and the absence of tools. Other communications and solutions that should be provided are buying internet quotas and using Wi-fi and IAIN Madura providing a learning system with the IAIN Madura e-learning website.